Imagining Time and Space in Universities Bodies in Motion - Matus, Claudia; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Imagining Time and Space in Universities presents critical theorizations of time and space to analyze discourses and practices of globalization and internationalization. As both dimensions have been understood in separate and hierarchical modes limited attention is given to cultural meanings embedded in these institutional policies and practices.
Keywords: Education; International education; Comparative education; Curriculums (Courses of study).; Education -- Curricula; Educational sociology; Higher education; Education -- History; Sociology; Education and sociology; Sociology, Educational; Education; Higher Education; Sociology of Education; History of Education; International and Comparative Education; Curriculum Studies; Sociology, general; Electronic books